2005
DOI: 10.1007/s10565-005-0124-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trichloroethylene and its metabolite trichloroacetic acid on the expression of vimentin in the rat H9c2 cell line

Abstract: Trichloroethylene (TCE) and its metabolite trichloroacetic acid (TCAA) are environmental contaminants with specific toxicity for the embryonic heart. In an effort to identify the cellular pathways disrupted by TCE and TCAA during heart development, we investigated their effects on expression of vimentin, a marker of cardiac differentiation. Previous studies had shown that the level of vimentin transcript was inhibited in rat embryonic heart after maternal exposure to TCE via drinking water. In the same study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The same researchers demonstrated a negative correlation between myocardial vimentin content and the actin-myosin sliding rate. The alteration in vimentin expression may be caused by changes in intracellular calcium concentrations [63]. Derangements of cytoskeletal proteins such as vimentin contribute to alterations in intracellular signaling, myocyte function, and coupling of myocytes to the extracellular matrix during cardiac hypertrophy and failure [20,21,61].…”
Section: 662mentioning
confidence: 99%
“…The same researchers demonstrated a negative correlation between myocardial vimentin content and the actin-myosin sliding rate. The alteration in vimentin expression may be caused by changes in intracellular calcium concentrations [63]. Derangements of cytoskeletal proteins such as vimentin contribute to alterations in intracellular signaling, myocyte function, and coupling of myocytes to the extracellular matrix during cardiac hypertrophy and failure [20,21,61].…”
Section: 662mentioning
confidence: 99%
“…Early studies focused on moderate to high levels of exposure. However, recent studies of gene expression in H9C2 cells suggest that there are biphasic curves with maximum effects between 10–100 ppb and again at 10–100 ppm (Caldwell et al, 2008; Selmin et al, 2005). As described by Drake et al (2006b), concentrations of TCE (8 ppb) close to the EPA maximum contaminant levels (5 ppb) are sufficient to alter cardiac hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has investigated the molecular mechanisms involved in cardiac toxicity of chlorinated hydrocarbons using animal and in vitro models [14,15]. In those studies, we identified genes whose expression was altered in rat embryonic heart and characterized how TCE and TCA altered their expression pattern in a dose-and time-dependent fashion.…”
Section: Introductionmentioning
confidence: 99%